Menopause and Mental Health - Shrivastava, Gunjan; Roshiya, Kalpesh Dhanji; Gohil, Disha Kamaljitsingh; Patadia, Hemantkumar (Journal of Neonatal Surgery, 2025)
Menopause is a significant biological phase in a woman's life, characterized by the cessation of menstruation and a drop in reproductive hormones. The psychological influence is sometimes overlooked, despite the fact that its physical effects are frequently acknowledged. Mood disorders, anxiety, depression, cognitive problems, and sleep disruptions are common among women and can have a major impact on their quality of life. Hormonal fluctuations, neurotransmitter imbalances, high cortisol levels, and oxidative stress are the main causes of many mental health issues. The biological processes behind these changes and their psychological impacts are the main topics of this review, which investigates the relationship between menopause and mental health. It also looks at coping mechanisms, such as lifestyle modifications like exercise and diet, psychological therapies like cognitive behavioral therapy (CBT) and mindfulness, and medicinal treatments like hormone replacement therapy (HRT) and antidepressants. Also included is the effect of COVID-19 on menopausal mental health, stressing the increased anxiety and disruptions to healthcare that women experienced throughout the epidemic. Research has advanced, but there are still gaps, especially in our knowledge of long-term mental health consequences, cultural variations in menopausal experiences, and the function heredity plays in mood regulation. Longitudinal studies, customized therapies, and incorporating mental health assistance into standard medical care should be the main topics of future research. Healthcare professionals can create more effective plans to assist menopausal women and lessen the stigma associated with this transition by filling in these gaps.